Local Knowledge in Managing Dioscorea hispida for Rural Food Security in West Java - Eva Carolina; Junardi Harahap (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2026)
Local knowledge in identifying, utilizing, and processing Dioscorea hispida (gadung) constitutes an important yet often overlooked component of rural food security. This study examines how such knowledge is produced, maintained, and practiced by communities in Darmaraja District, Sumedang Regency, West Java. A qualitative approach was employed through in-depth interviews and field observations involving eight informants with varying degrees of experience in gadung utilization. The findings reveal that local communities possess detailed ecological knowledge that enables them to identify gadung based on morphological characteristics and seasonal harvesting cycles, particularly during the dry season. Despite its natural cyanide content, gadung is rendered safe through a complex, multi-stage detoxification process, including slicing, drying, soaking, repeated washing, and steaming, which may take up to 9–10 days. This process demonstrates not only technical expertise but also embedded cultural values such as patience, risk awareness, and intergenerational knowledge transmission. Beyond subsistence, gadung contributes to rural livelihoods through small-scale economic activities, particularly in the production of chips, while also reflecting gendered divisions of labor in resource management. Moreover, gadung carries symbolic meanings embedded in oral traditions and local expressions, indicating its broader role within the cultural system. This study argues that local knowledge surrounding gadung represents a multidimensional knowledge system that integrates ecological adaptation, economic resilience, and cultural meaning. As such, it plays a critical role in strengthening sustainable food security by enabling communities to utilize marginal and potentially hazardous resources in adaptive and culturally embedded ways.